Analysis of development trends of the Krasnodar territory tourist-recreational complex in modern conditions - M. K. Kovaleva (Новые технологии, 2017)
The article analyzes dynamics of key parameters of the functioning of the tourist sphere of the Krasnodar Territory. It is indicated that relatively new directions of tourism (rural, yacht, water, cruise, wine, gastronomic, ethnographic) are constantly being formed and developing in the territory of the region, and active kinds of tourism (cycling, hiking, skiing, etc.) are developing. Among the main directions of the development of the tourist complex of the region are creation of the mountain-climatic resort of Lagonaki and the objects that ensure its functioning, as well as creation of the tourist and recreational cluster Abrau-Utrish (the cities of Novorossiysk and Anapa). The importance of effective management of the objects of the Olympic heritage in the context of the realization of the tourist potential of the region is noted.